Using Technology to Improve English as a Foreign Language (EFL) Assessment - Ilahi, Witri Nur; Oktaviana, Fadilla; Heryatun, Yayu; Ilzamudin, Ilzamudin; Tarihoran, Naf'an (English Education, Linguistics, and Literature Journal, 2025)
Abstract: Technology is now a key component of the assessment process used in English as a Foreign Language (EFL) instruction, helping to increase student performance. A more thorough and precise technique to develop students' speaking and listening abilities is through the use of technology in EFL assessments. This study aims to investigate how much the use of technology in EFL assessments can affect students' speaking and listening skills development. It also seeks to define the benefits and difficulties of applying such technology. The research approach employed was a thorough literature analysis, which included an examination of numerous books, journal articles, and other pertinent materials about the application of technology to the evaluation of speaking and listening abilities in an EFL setting. The purpose of this analysis was to collect empirical data regarding the advantages and disadvantages of using this technology. The findings demonstrate that using technology into EFL assessments can greatly enhance the standard of evaluating students' speaking and listening abilities. Via e-learning apps and platforms, students can receive timely and organized feedback that helps them improve their English communication skills and fix errors. But there are still problems to be solved, like digital skills, technology preparedness, and adjusting to new techniques. The study's conclusion is that using technology into EFL assessments helps students' speaking and listening abilities. Educational institutions may fully utilize the potential of technology to enable more efficient and integrated English language learning by giving teachers the proper training, building the necessary technological infrastructure, and putting the right techniques into practice.